Beyond checklists: Using clinic ethnography to assess the enabling environment for tuberculosis infection prevention control in South Africa. - Stella Arakelyan; Hayley MacGregor; Anna S Voce; Janet Seeley; Alison D Grant; Karina Kielmann (Public Library of Science (PLoS), 2022)
Sub-optimal implementation of infection prevention and control (IPC) measures for airborne infections is associated with a rise in healthcare-acquired infections. Research examining contributing factors has tended to focus on poor infrastructure or lack of health care worker compliance with recommended guidelines, with limited consideration of the working environments within which IPC measures are implemented. Our analysis of compromised tuberculosis (TB)-related IPC in South Africa used clinic ethnography to elucidate the enabling environment for TB-IPC strategies. Using an ethnographic approach, we conducted observations, semi-structured interviews, and informal conversations with healthcare staff in six primary health clinics in KwaZulu-Natal, South Africa between November 2018 and April 2019. Qualitative data and fieldnotes were analysed deductively following a framework that examined the intersections between health systems 'hardware' and 'software' issues affecting the implementation of TB-IPC. Clinic managers and front-line staff negotiate and adapt TB-IPC practices within infrastructural, resource and organisational constraints. Staff were ambivalent about the usefulness of managerial oversight measures including IPC protocols, IPC committees and IPC champions. Challenges in implementing administrative measures including triaging and screening were related to the inefficient organisation of patient flow and information, as well as inconsistent policy directives. Integration of environmental controls was hindered by limitations in the material infrastructure and behavioural norms. Personal protective measures, though available, were not consistently applied due to limited perceived risk and the lack of a collective ethos around health worker and patient safety. In one clinic, positive organisational culture enhanced staff morale and adherence to IPC measures. 'Hardware' and 'software' constraints interact to impact negatively on the capacity of primary care staff to implement TB-IPC measures. Clinic ethnography allowed for multiple entry points to the 'problematic' of compromised TB-IPC, highlighting the importance of capturing dimensions of the 'enabling environment', currently not assessed in binary checklists.